Efficacy of a partial hospital programme for adults with eating disorders. (14th March 2018) - Brown, Tiffany A.; Cusack, Anne; Anderson, Leslie K.; Trim, Julie; Nakamura, Tiffany; Trunko, Mary Ellen; Kaye, Walter H.
Abstract: Partial hospital programmes (PHPs) have demonstrated efficacy in the treatment of eating disorders (EDs); however, few programmes have examined long‐term outcomes across diagnoses, including subtypes of anorexia nervosa (AN). The present study examined the effectiveness of PHP for adult patients ( n = 243) with AN‐restricting subtype ( n = 79), AN binge/purge subtype ( n = 46), and bulimia nervosa ( n = 118). These patients tended to have long‐standing courses of illness (43%, illness duration >7 years) and high levels of psychiatric comorbidity (92.2%). Patients completed questionnaires at admission, discharge, and follow‐up, M ( SD ) = 11.50 months (5.29). Through follow‐up, all diagnoses demonstrated significant improvements in weight, ED psychopathology, and comorbid symptoms, with some exceptions for the AN binge/purge group. In exploratory analyses, 49% of patients met criteria for full or partial remission at discharge and 37% at follow‐up. Results provide support for the effectiveness of PHP in improving ED outcomes in a severe sample through longer‐term follow‐up.